Analisis Kesalahan dalam Struktur Tata Bahasa Siswa dalam Menerjemahkan Teks Naratif - Kiromil Baroroh (UIN Alauddin Makassar, 2024)
This research aims to discover the errors in students’ narrative text translation based on the Surface Strategy Taxonomy. The descriptive qualitative method was used in this research. The populations were the ninth-grade students of SMP Negeri 1 Ambarawa in the academic year 2022/2023. Specifically, 10 students from the IX A class were randomly chosen as the subject. The instrument used was a translation task entitled Kancil dan Buaya. The data was collected by administering the translation test in 90 minutes. Surface Strategy Taxonomy was used to identify the errors in analyzing the data. The results showed that the most frequent error made by students was misformation, while the least common error was misordering. In addition, the component of misformation in which the students made errors the most was the alternating form. Hence, this indicates that the student’s English proficiency, mainly in grammar, is still poor. Further researches are suggested to investigate more the causes of errors that occur in students’ translation through interviews or questionnaires in order to achieve more in-depth data.